Cognitive-Strategy Based Method Vs. Metacognitive-Strategy Based Method: The Impact on Listening Comprehension - Erniwati, Erniwati; Mertosono, Sudarkam Ramlan; Arid, Muhammad; Refnaldi, Refnaldi (English Department FBS UNP, 2024)
The ability to speak English is very important, but it will not be successful without being supported by the ability to listen to understand the verbal language. The poor listening skills of the English Education students at Tadulako University in the final exam of the Listening for General Communication course became the basis for conducting this study. The results of the test showed that around 80% students failed the course with percentage intervals of comprehension levels of 0-39%. Therefore, this study is carried out to specify if using Cognitive-Strategy Based Method and Metacognitive-Strategy Based Method is effective in improving the participants’ listening comprehension as well as to compare the effectiveness of the two strategies. This study applied experimental design involving 80 samples evenly distributed in two classes. One class was instructed using Cognitive strategy, while the other one was taught using Metacognitive strategy. Results of data analysis demonstrated that both the Cognitive and Metacognitive strategies effectively improve the participants’ listening comprehension. There is no significant difference in terms of the effectiveness of both strategies in improving listening skills of the participants. In practice, they support each other resulting in learners better listening comprehension.